The prison in crisis: notes for a regulatory reform of parole - Chaiña Durán, Renzo Joel (2024)
This paper is based on the premise that parole assumes the configuration of rights and the objective was to reach an approximation to the implications of such a postulate in the Peruvian legal system. For that purpose, an analysis of the national and international literature that deals with the dogmatic and applicational dimensions of these figures was carried out. It was concluded that it is not possible to restrict the legal application of early release, regardless of the seriousness of the crime or sentence imposed, and that the concession factors to be legislated must be based on empirical evidence related to recidivism.